Neutron generation during pulsed discharge in deuterium; Technical Physics Letters; Vol. 37, iss. 7 - Lomaev M. I.; Dudkin G. N. Gennadiy Nikolaevich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Sorokin D. A.; Tarasenko V. F. Victor Fedotovich; Yalovets A. P. (2011, 2011)
Title screen